The elaboration of the notion of «pure natural state» in Francisco Suárez’s 'Tractatus de gratia'. The view of André de Muralt - Fernández Polanco, Valentín (Logos. Anales del Seminario de Metafísica, 2020)
Francisco Suárez (1548-1617) has provided the modern political philosophers with thenotion of «pure natural state» as endowed with its own objective reality, a key conceptual tool that theywere going to use in order to develop their political and juridical thought. In this paper we follow thetrail of two medieval sources that Suárez has used in the elaboration of this notion: the grace’s Christiantheology and the formal distinction ex natura rei from Duns Scotus.
Keywords: Duns Scotus; formal distinction ex natura rei; Francisco Suárez; pure natural state; theology of grace